Síntese de 3-alcoxiacrilamidas a partir de tricloroacetil enol éteres - Mello, Débora Lombe de (2012)
This work reports a effective method for the preparation of a series of the new 3-alkoxy acrylamides of general formula R3HNC(O)CR1=CR2(OR), where R/ R1/ R2 = Et/H/H, Me/H/Me, -(CH2)2-/H, -(CH2)3-/H; R3 = Allyl, n-Pr, Bn, Phenetyl. However, the 3-alkoxy acrylamides where R/ R1/ R2 = Et/H/H/, Me/H/Me, R3 = Bn, have already been described in the literature. The 3-alkoxy acrylamides were obtained through three reaction steps. The first step, β-alkoxyvinyl trichloroacetyl ketones were synthesized through the acylation of enolethers using trichloroacetyl chloride as the acylating agent. In the second step, β-alkoxyvinyl trichloroacetyl ketones were converted to the corresponding β-alkoxyvinyl carboxylic acids from a basic hydrolysis using a 1 M sodium hydroxide solution. In the third step, β-alkoxyvinyl carboxylic acids were treated with thionyl chloride, using toluene as solvent, leading to the corresponding acyl chlorides intermediaries, which were not isolated. The acyl chlorides were reacted with primary amines such as allylamine, propylamine, benzylamine, and phenethylamine under basic catalysis of triethylamine, furnishing a new series of 3-alkoxy acrylamides in good yields of 48-90%. The 3-alkoxy acrylamides obtained in this study were identified by 1H and 13C Nuclear Magnetic Resonance spectroscopy, Mass spectroscopy and Elemental analysis. Keywords: 3-alkoxy acrylamides, β-alkoxyvinyl carboxylic acids, β-alkoxyvinyl trichloroacetyl ketones, acyl chlorides, amines